HTC One (M8) for dummies - Hughes, Bill 1960- (John Wiley & Sons, Inc., 2015)
Are you the proud owner of an HTC One, but a bit baffled by its seemingly endless capabilities? Hughes takes the intimidation out of the technology and offers plain-English explanations for making the most of your new smartphone.